Re-thinking complex, fluid and contradictory knowledge(s) in higher education - Mago, Malo William (South African Journal of Higher Education, 2016)
Turbulent economic, political, social and cultural environments, coupled with the unpredictable natural environment, are currently the most prominent features of the state of the world. While in the past these phenomena were more simple, straightforward and certain, of late they have become complex, unpredictable and often contradictory to the previous ‘norm’, thus presenting challenges that are more difficult to understand and resolve. Consequently, the realisation has emerged that contemporary education systems, largely based on present disciplinary grounded knowledge, are no longer adequate. In the light of the need for scholars in all fields of knowledge to rethink how broader, open-ended inquiries of knowledge production can be pursued in higher education, I argue that the ‘knowledge’ that is perceived as inadequate because of its complexity, uncertainty and contradictory nature, should be revisited through multi-dimensional knowledge production processes underscored by socio-cultural perspectives. Key words: complexity, uncertainty, contradiction, ways of knowing, knowledge